Reaction paths and transition states of the C-C and C-H bond cleavage in the aromatic anthracene and phenanthrene molecules - Shanshal, Muthana Abduljabbar; Al-Yassiri, Muntadhar Abdulbary; Yusof, Qhatan Adnan (European Journal of Chemistry, 2016)
The reaction paths of the C-C and C-H bond cleavage in the anthracene and phenanthrene aromatic molecules are studied by applying the ab-initio DFT method. It is found that the C-C bond cleavage proceeds via a singlet aromatic transition state, compelled through a disrotatoric ring opening reaction. A suprafacial H atom shift follows the transition state, leading to the formation of a methylene -CH2 and an acetylenic or allenic moiety. The calculated activation energies for anthracene range from 158.81-208.90 kcal/mol and the reaction energies from 96.106-156.976 kcal/mol. For phenanthrene, the energy values are 157.39-202.34 kcal/mol and 62.639-182.423 kcal/mol, respectively. For the C-H cleavage reactions, the calculated reaction energies for all C-H bonds in both molecules are almost similar, 116-117 kcal/mol. The activation energy values for anthracene and phenanthreneare 149.75-161.27 and 161.24-163.00 kcal/mol, respectively.